Global EEG coherence as a marker for cognition in older adults at risk for dementia. (16th December 2019) - Laptinskaya, Daria; Fissler, Patrick; Küster, Olivia Caroline; Wischniowski, Jakob; Thurm, Franka; Elbert, Thomas; von Arnim, Christine A. F.; Kolassa, Iris‐Tatjana
Abstract: Quantitative electroencephalography (EEG) provides useful information about neurophysiological health of the aging brain. Current studies investigating EEG coherence and power for specific brain areas and frequency bands have yielded inconsistent results. This study assessed EEG coherence and power indices at rest measured over the whole skull and for a wide frequency range as global EEG markers for cognition in a sample at risk for dementia. Since global markers are more reliable and less error‐prone than region‐ and frequency‐specific indices they might help to overcome previous inconsistencies. Global EEG coherence (1–30 Hz) and an EEG slowing score were assessed. The EEG slowing score was calculated by low‐frequency power (1–8 Hz) divided by high‐frequency power (9–30 Hz). In addition, the prognostic value of the two EEG indices for cognition and cognitive decline was assessed in a 5‐year follow‐up pilot study. Baseline global coherence correlated positively with cognition at baseline, but not with cognitive decline or with cognition at the 5‐year follow‐up. The EEG slowing ratio showed no significant association, neither with cognition at baseline or follow‐up, nor with cognitive decline over a period of 5 years. The results indicate that the resting state global EEG coherence might be a useful and easy to assess electrophysiological correlate for neurocognitive health in older adults at risk for dementia. Because of the small statistical power for the follow‐up analyses, the prognostic value of global coherence could not be determined in the present study. Future studies should assess its prognostic value with larger sample sizes. Abstract : The study introduces global coherence across all regions and a wide range of frequency bands as a robust electrophysiological marker for cognition in older adults with a higher risk for developing dementia. In addition, it presents longitudinal electrophysiological data for coherence‐cognition relationships. The study results suggest that global EEG coherence may be currently of higher benefit in research and in clinical application than region‐ and frequency‐specific coherence measures.